Variasi Anatomi Pola Percabangan Arcus Aorta - Handy Winata (Jurnal Kedokteran Meditek, 2019)
Aortic arch is part of the pars thoracic aorta, located in the superior mediastinum. Its function is to carry oxygenated blood to all parts of the body in systemic circulation. From five different studies, all of them showed variations of the aortic arch branching patterns. This article discusses the variation of aortic arch branching patterns using the Natsis classification. The study found that the variations in the branching pattern are mainly of type I and type II.